Radial basis function networks for communication channel equalisation - Chandra Kumar, P. (2008)
This thesis presents the application of a minimal radial basis function (RBF) neural network, referred to as MRAN (Minimal Resource Allocation Network) for communication channel equalisation and co-channel interference rejection. Unlike most classical RBF neural networks with the number of hidden neurons fixed apriori, the MRAN network structure is dynamic.